Entrepreneurial Innovation and the Performance of a Sustainable Organization: A Case Study of a Faith-Based Non-Profit Organization: - Wulandari, Respati (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
It is essential for both non-profit and for-profit organizations to maintain sustainable performance. Innovation functions as a crucial performance metric in attaining outstanding results. This study represents a distinctive contribution to the topic of entrepreneurship by concentrating on its use within religious non-profit organizations. The Catholic Archdiocese of Jakarta, situated in Indonesia, possesses a historical legacy spanning nearly two centuries. Throughout its history, the Catholic Church has faced numerous internal and external challenges and dynamics. Priests function not just as spiritual leaders but also as catalysts for innovation within their own parishes. This article analyzes the impact of innovations introduced by parish priests on the Church's performance, based on interviews with 19 parish priests in leadership positions. Furthermore, it examines the tactics utilized by these priests to surmount problems faced in metropolitan regions. This study will underscore the importance of innovation and present new research opportunities for scholars, social managers, and practitioners in this field of study.